PROTOTYPE OTOMATIS SISTEM MONITORING PEMELIHARAAN TOKEK GURUN BERBASIS IoT PADA PLATFORM THINGSPEAK MENGGUNAKAN ALGORITMA C4.5 - Anderias Eko Wijaya; Roby Muhromi (Jurnal Teknologi Informasi dan Komunikasi, 2022)
The Leopard Gecko is a reptilian species that thrives in desert regions with a humidity level of around 60%. Native to Pakistan, this exotic reptile captivates many reptile enthusiasts due to its unique skin color and pattern, aligning with its name. However, there are challenges in the care of Leopard Geckos, particularly among novice reptile enthusiasts who may lack comprehensive knowledge of proper care. This lack of knowledge can lead to issues such as tail dropping and illness, sometimes resulting in fatalities. To ensure the well-being of Leopard Geckos in captivity, it is crucial to create an environment that mimics their natural habitat, preventing severe issues such as tail loss, damaged skin, or even death. To address these concerns, an Internet of Things (IoT)-based System for Monitoring the Care of Leopard Geckos is developed, employing the C4.5 algorithm and the Thingspeak platform. The hardware used includes Arduino Uno, DHT11 sensor, LDR sensor, Ultrasonic sensor, Servo Motor, and ESP8266 Wifi Module. The research findings indicate that if the temperature exceeds 32°C and humidity drops below 60%, the lamp turns off, and the mist maker activates. Conversely, if the temperature falls below 32°C and humidity surpasses 60%, the lamp turns on, and the mist maker deactivates.